PENGARUH RUANG TERBUKA DAN PENGKONDISIAN UDARA BUATAN TERHADAP KUALITAS UDARA PADA PERUMAHAN : (STUDI KASUS: PERUMAHAN J. CITY JOHOR) - Ritonga, Isniar; Martha Mulia, Endi; Calista; SILVIYANA, VIVI (LPPM ISTP, 2025)
This study aims to analyze the influence of Green Open Space (GOS) and artificial air conditioning on air quality in the J. City Johor residential area, Medan. The research was conducted through observational methods by measuring temperature, humidity, and wind speed over seven consecutive days in three different zones: GOS, indoor areas, and outdoor areas. The results show that although indoor temperatures generally fall within the standard thermal comfort range (24–27 °C), humidity levels often exceed the recommended standard (>60%), particularly during midday and afternoon hours. This study highlights the importance of optimal GOS planning and adequate ventilation systems to ensure healthy and comfortable air quality in tropical residential environments.